Evaluasi Sistem Perpipaan Plambing Gedung Asrama Mahasiswa ITS Surabaya - Agustina, Nuria; Nurul Jannah Asid; Rizki Astri A (AGREGAT, 2024)
ITS Surabaya Student Dormitory Building uses PDAM clean water services and is also equipped with a fire extinguishing installation whose distribution network system uses clean water. As students' needs increase, their need for clean water will also increase. And because of this, this building often experiences problems distributing clean water during peak usage hours due to simultaneous use, there is a decrease in the flow of each unit of piping equipment due to uneven installation of the clean water distribution system. Therefore, the distribution system in pipes requires special handling which often experiences problems in terms of quantity, pressure and continuity of water. The aim of this research is to analyze the magnitude of energy loss in the plumbing pipe network in the ITS Surabaya Dormitory Building, and also to analyze the causes of closed pipes experiencing energy loss. At which point the energy loss is highest, so is the remaining energy at the last pipeline node. The method used in this research is a quantitative method by analyzing the condition of the existing pipe network in clean water installations and fire extinguishing installations in terms of pipe dimensions, pipe length and reservoir elevation which will then be carried out by running tests with the program to find out how much The large energy losses that occur in plumbing pipe networks are assisted by a simulation program using Epanet 2.2. From the results of this research, there are several conclusions that the results of the analysis of the Clean Water pipe network of the ITS Surabaya Student Dormitory Building for clean water installations have the highest velocity (Velocity) of 0.2 m/s in pipe 15 on the 1st Floor, and the sprinkler pipe has a velocity (Velocity). ). ) the highest is 0.08 m/s on pipe 01 Floor 2. There are still many pipes whose speed is less than 0.1 m/s, which means the pipe speed in the network does not meet the design criteria. And for the pressure of the clean water pipe network and sprinklers at all node points with a value of ≥0.5 bar (according to planning standards). Based on the results of running unit headloss, the clean water pipe network and sprinklers have a value of <10 m/Km (according to planning standards) and no pipes experience negative pressure or pressure drop.